Children in Digital Age – Slovakian Perspective - Koromház, Peter (Children in Digital Age, 2025)
Abstract:The chapter examines the legal and regulatory frameworks that govern the protection of children’s rights in the digital environment in the Slovak Republic. It explores the multifaceted risks children face online, such as cyberbullying, exposure to harmful content, and violations of privacy, while also acknowledging the opportunities for education, socialization, and personal development that the digital space provides. Emphasis is placed on the national strategy for the protection of minors in the digital environment and the analysis of the right to privacy and the right to be forgotten, the right to be heard, the right to information and the right to education.Keywords: child protection, digital environment, right to by forgotten, right to information, right to be heard